Effect of Postprandial Glucose Dips on Hunger and Energy Intake in 1102 Subjects in US and UK: The PREDICT 1 Study. (29th May 2020) - Berry, Sarah; Wyatt, Patrick; Franks, Paul; Blundell, John; O'Driscoll, Ruairi; Wolf, Jonathan; Hadjigeorgiou, George; Drew, David; Chan, Andrew; Spector, Tim; Valdes, Ana
Abstract: Objectives: Modulating appetite and energy intake at an individual level is key to successful weight loss interventions. Given the high individual variability to weight loss diets, large scale and high-precision studies are needed to formulate a personalized approach. The PREDICT 1 study (NCT03479866) examined the impact of rises and dips in postprandial glucose on subsequent appetite and energy intake. Methods: A dietary intervention study of 1102 healthy individuals from the US and UK assessed glycemic responses to standardized meals of different macronutrient content and self-selected meals (>100, 000) over a 13-d period at home using a continuous glucose monitor. Glucose responses were defined as; baseline (0 to −30 min pre-meal average), rise (max % increase above baseline 0–2 h) and dip (max % dip below baseline 2–3 h). Hunger was recorded using visual analogue scales and energy intake was measured using weighed food records, barcoding and photographs via a mobile app. Results: Glucose dips (compared to rises) were more closely correlated with the increase in hunger, reduced time until next meal, and increased energy consumption (at the next meal and over 24 hrs). Following 8522 standardised breakfasts (n = 1070), individuals with the largest dips in glucose (Q4; 18%) vs. those with the smallest dips (Q1; 0%), had a higher subsequent glucose rise (mean; 95%CI) (6%; 3, 9); reported greater hunger 2–3 hrs post meal (9%; 6, 12); chose to eat earlier (–18 mins; 10, 26) and consumed more energy at both the next meal (57 kcal; 33, 81) and over the next 24 hrs (288 kcal; 215, 361); all P  < 0.001. Glucose dips were a common phenomenon, occurring in 40% of individual's (following 1812 home meals ranging 400–600 kcal and 30–60% energy from carbs). However, the timing and size of the dip was differentially associated with insulin sensitivity and BMI; late dippers (4 h dip) were less insulin sensitive and had higher BMI compared with early dippers (2 h dip). Conclusions: In the most comprehensive study to date, we demonstrated that postprandial glucose dips occur frequently and are associated with hunger, energy consumption and insulin sensitivity in real world conditions. Therefore, targeting susceptible individuals to reduce their glucose dips may enable optimal weight control by reducing postprandial appetite and energy intake. Funding Sources: NIHR, Wellcome Trust, Zoe Global Ltd.